Structural, optical and thermal studies of lead lithium borate glasses doped with copper oxide - I. Kashif; A. Ratep (Discover Materials, 2025)
Abstract This study investigated the thermal, optical, and structural properties of copper-doped lithium lead borate glass. According to infrared investigation, copper ions operated as network modifiers in all glass samples. The increased copper oxide content reduced the density and molar volume. All glass samples had a refractive index of approximately 1.5 in the ultraviolet and visible ranges, except for the sample with a lower CuO content (5 mol%). Therefore, a glass sample can be used as an optical filter. The sample with 5 mol% CuO served as a sunglass filter, protecting it from UV light by removing the ultraviolet area. Furthermore, the CuO sample with 35 mol% functioned as a cutoff filter, cutting off the ultraviolet and visible regions. Furthermore, samples containing 10, 15, or 25 mol% CuO can be utilized to create a green filter.